Understanding Plant Reproductive System through Animated Videos with Project-Based Learning Activities - I Gusti Ayu Irma Dewi Jumaheni; Ni Wayan Rati; I Komang Sudarma (Universitas Pendidikan Ganesha, 2021)
This research was conducted based on the lack of learning media that can be used through online and offline learning in the Covid-19 pandemic situation, limiting face-to-face learning. The main purpose of this study was to determine the development process and the validity of project-based learning-oriented animation videos on the theme of saving living things, especially on the topic of plant reproduction. The development of this animated video media used the ADDIE development model. The research subjects for developing project-based learning-oriented animation videos were two content experts, two learning design experts, two learning media experts, individual trials, and small group trials. The method of data collection was in the form of a questionnaire. The results of data analysis showed that the average score of material experts was 4.79 with very good qualifications, design experts 4.65 with very good qualifications, media experts at 4.62 with very good qualifications, individual tests of 4.8 with very good qualifications, and a small group test of 4.74 with very good qualifications. Thus, the overall validity of Project-Based Learning-oriented animation video media was in the range of 4.01 < X 5.01 with